Keyboard warrior, online predator or cyber bully? The growing menace of child exposure to internet harm based on research evidence - Yusuf, Sarina; Idris, Khairuddin; Abu Samah, Asnarulkhadi; Ibrahim, Adamkolo Mohammed; Ramli, Nor Sabila; Ibrahim, Muhamad Shamsul; A. Rahman, Nur Atikah (Universiti Putra Malaysia Press, 2020)
The internet has come along with a myriad of positive and negative challenges. One of the positive developments is the increased access for all age categories, especially people of young ages; however, it is not without a side effect. A cyberbullying threat has become interesting areas of research over the years because of the importance of the concepts toward understanding children’s online behaviours and making the internet safe again for the kids to surf. Thus, this article seeks to provide a further understanding of the phenomenon by reporting the findings of a study performed in Selangor, a state of Malaysia. A questionnaire was administered to 375 respondents selected using stratified random sampling from a population of 6,671 primary and secondary school pupils aged 9 to 16 years. The key findings revealed that most children had been involved in the act of cyberbullying. Interestingly, most of them were aware of online threats but did not know that it was bad behaviour. However, most of them were rarely involved in a sex-related cyberbullying incident. A collective approach to guarantee the internet safety of children and balance their online prospects and risks is recommended to ensure children’s online safety.